Explaining the structure of intellect and ignorance based on three components of thought and present and action with emphasis on the description of mulla Sadra's sufficient principles. - BIBI bahareh Fakoor yahyayi; abbas javareshkian; JAHANGIR MASOODI (حکمت اسرا)
Imam Ja'far Sadegh (AS) in the noble hadith of intellect and ignorance, introduces the necessity of human guidance to know the armies of intellect and ignorance. Sadr al-Muta'allehin Shirazi has paid special attention to the explanation of this hadith in his book Sharh Sufficient Principles.Examining the seventy-five armies of reason and ignorance, from the perspective of the mentioned components and their principles and results, moral virtues and vices can be divided into six areas: principles and principles, thoughts, thoughts and circumstances, thoughts and actions, thoughts and circumstances and actions. He also categorized the fruits and works of these forces. With this explanation, we reach the conclusion that in order to achieve true human guidance, a model of moral characteristics must be set that looks at all aspects of human existence and in terms of the interrelationships of the three sides of human existence, can draw the steps of human moral behavior to The rule of the intellect, the human virtues and moral virtues have the opportunity to appear and manifest, and to the extent of the activity of divine perfections, worldly and otherworldly happiness is achieved.